WHAT DRIVES MORE INTEREST IN BUYING SKINCARE? ONLINE CUSTOMER REVIEW OR ONLINE CUSTOMER RATING (International Journal of Innovative Technologies in Economy, 2025)
The value of skincare is becoming more widely recognized, and the skincare business in Indonesia is expanding significantly. Through the marketplace platform, this study seeks to ascertain what motivates Generation Z consumers to purchase skincare products based on online user ratings and reviews. Questionnaires were employed in the study's quantitative data collection methodologies. The study's participants were Cirebon City teenagers between 14 and 18, and 400 responders were found using the Slovin formula. Data analysis was conducted using SEM-PLS, a statistical method that incorporates partial least squares. The data was examined through the use of SEM-PLS, a technique known as Structural Equation Modeling-Partial Least Square. The findings demonstrated that online consumer ratings and reviews significantly influence purchasing intention. These two independent variables can influence Generation Z's combined inclination to buy skincare products. Online reviews from customers play a crucial role in influencing the decision to buy skincare items. This suggests that Generation Z accepts and believes user reviews that provide product details, usage experiences, benefits, and drawbacks, as well as information that helps prospective customers comprehend the makeup of skincare products. To stimulate Generation Z's interest in purchasing skincare products, skincare business actors can use the study's findings to help them create digital-era marketing strategies that work. They can also try to get customers who have already purchased skincare products to write reviews.